Defining a Strategy for Using the Intelligent Transport Systems Tool in the Slovak Republic - Michal BALLAY; Jozef KUBÁS; Katarína ZÁBOVSKÁ (Communications of International Proceedings, 2021)
The article focuses on the benefits of using intelligent transport systems in road transport. Currently, the development of the company is fundamentally influenced information and communication technologies. This trend has a significant impact also on the transport process and transport services. Emphasize the benefits and concept of intelligent transport systems as a tool for traffic regulation and management, is the main part of this article. In this context, we focused on the Slovak Republic, while using these ingenious multimodal and interdisciplinary tools, we are for a given state identified a strategic option. For the area of intelligent transport systems, we chose the SWOT method. Using brainstorming on the topic of strengths, weaknesses, opportunity and threat, we identified the individual factors.
Keywords: Road Transport; Intelligent Transport Systems; Slovak Republic; SWOT Analysis